Stability and density analysis of mango bark and mango leaf nanofluids - Chen, J. L. T.; Oumer, A. N.; Azizuddin, Abd Aziz (IOP Publishing, 2020)
Thermal conductivity is one of the primary properties for nanofluids application investigated by many researchers. However, there are other factors such as stability and density that need to be considered to reduce sedimentation, pressure drop as well as sustain the enhanced thermal physical properties of nanofluid. The purpose of this study is to investigate and analyse the stability and density of mango bark (MB) and mango leaf (ML) nanofluids as well as hybrid nanofluids between mango bark and leaf with SiO2 and TiO2. The stability of nanofluids was measured using sedimentation method. The nanofluids arranged in order of pure ML nanofluid with increasing volume concentration of 0.25%, 0.50% and 1.00% followed by MB nanofluid, ML/SiO2 nanofluid, MB/SiO2 nanofluid, ML/TiO2 nanofluid and MB/TiO2 nanofluid. The density of nanofluids was measured using KEM DA-640 density meter and calculated using mixture rule equation. The results show that the stability of the nanofluids started to show sedimentation after 1 day of storing. Mango bark nanofluids were more stable than mango leaf nanofluids. At 1% concentration, MB nanofluid has the highest density (0.9981) followed by MB/TiO2 (0.9970), ML/TiO2 (0.9964), ML (0.9963), MB/SiO2 (0.9962) and ML/SiO2 (0.9962). Density of nanofluids have small increment with volume concentration. Meanwhile, the density of nanofluids have small decrement with volume concentration using analytical calculation. The results also shows small average error of 0.17% between experiment and analytical calculation.